Nursing Care for Oxygen Deficiency in Patients with Pulmonary Tuberculosis - Marsha Wulandari Marsha; Wira Heppy Nidia; Indri Ramadini; Herwati; Efitra (Journal of Applied Holistic Nursing Science, 2025)
Background: Pulmonary tuberculosis remains a significant global health problem, especially in developing countries. Pulmonary tuberculosis can cause symptoms such as chronic cough, fever, weight loss, and fatigue. If not treated immediately, it can lead to serious complications and death. The objective of this study is to describe nursing care for patients with oxygen deficiency disorders in pulmonary TB patients in the pulmonary ward of Dr. M. Djamil General Hospital in Padang. Methods: This is a descriptive qualitative study. The study was conducted in the Pulmonary Ward of Dr. M. Djamil General Hospital in Padang. The study period spanned from December 2024 to June 2025. The study population was comprised of all pulmonary TB patients with oxygen deficiency in the Pulmonary Ward of Dr. M. Djamil General Hospital in Padang. One patient diagnosed with primary pulmonary TB in the Pulmonary Isolation Room at Djamil General Hospital in Padang was selected using purposive sampling for a study that involved interviews and measurements. Data collection methods included interviews, measurements, physical examinations, and documentation. Results: The results showed complaints of shortness of breath, coughing up phlegm, difficulty sleeping, night sweats, and paleness. The nursing diagnosis that was established was gas exchange disorder. The nursing plan and its subsequent implementation encompassed respiratory monitoring, oxygen therapy, chest physiotherapy, and the promotion of effective coughing. The results showed reduced shortness of breath, reduced sputum production, and no more visible signs of illness. The evaluation results showed that shortness of breath had decreased, coughing up sputum had decreased, shortness of breath was no longer visible, skin color was no longer pale, and there was no longer any visible nasal flaring. Conclusion: Nursing implementation was carried out as part of the nursing plan, which was developed with the expectation that the results achieved would be in line with the objectives and criteria that had been set. Nursing implementation was carried out over a 5-day treatment period in the form of respiratory control, chest physiotherapy, and effective coughing.